AB1049 CLINICAL SPECTRUM AND THERAPEUTIC MANAGEMENT OF AUTO-IMMUNE MYELOFIBROSIS: A NATION-WIDE STUDY OF 30 CASES. (13th June 2020) - Mertz, P.; Chalayer, E.; Sibilia, J.; Gottenberg, J. E.; Korganow, A. S.; Arnaud, L.; Martin, T.
Abstract : Background: Little is known about autoimmune myelofibrosis (AIMF), a rare entity that can occur alone or in association with another autoimmune disease (AID) and is responsible for bone marrow (BM) failure and life-threatening complications. Objectives: We conducted a nationwide retrospective observational study of AIMF cases to better characterize the epidemiology, clinical presentation and evolution of this rare entity. Methods: The aim of the study was to analyze the characteristics of AIMF and the nature and indication of treatments currently used. Response to treatment was evaluated by the revised Tefferi et al. response criteria. Results: Among 30 cases of AIMF, the sex ratio (F/M) was 4:1 and the median age at diagnosis was 37 years (interquartile range 30–49). AIMF was diagnosed after the onset of an associated AID in 12 cases and concomitant to an AID in the remaining 18 cases. The most frequently associated AID was systemic lupus erythematous, followed by Sjögren syndrome. All cases consisted of reticulin fibers, and no collagen fibrosis was described. More than 50% of cases showed complete response after first-line therapy, with glucocorticoids (GC) in 28 cases. Half of the cases had treatment complications mainly related to GC therapy. Conclusion: Diagnosis of AIMF remains challenging in the absence of a validated set of diagnosis criteria, and must always be searched in the presence of hematological abnormalities at onset or during follow-up of AID. Clinical context, search for mutations and pathology findings can help differentiating this rare disease from a clonal pathology. GC is currently an effective first-choice therapy for AIMF, but a high rate of GC dependency and long-term complications indicate the need to find new sparing drugs. Disclosure of Interests: PHILIPPE MERTZ: None declared, Emilie Chalayer: None declared, Jean Sibilia: None declared, Jacques-Eric Gottenberg Grant/research support from: BMS, Pfizer, Consultant of: BMS, Sanofi-Genzyme, UCB, Speakers bureau: Abbvie, Eli Lilly and Co., Roche, Sanofi-Genzyme, UCB, Anne-Sophie Korganow: None declared, Laurent Arnaud: None declared, Thierry Martin: None declared